The Construction of Centralized Disciplinary Leadership in Developing Moderate Attitudes in Private Madrasah Tsanawiyah - Umar, A.; Rofiq, Muhammad; Nasikhin, Nasikhin; Panaemalae, Abdulraya; Hassan, Zainudin bin (International Journal of Social Learning (IJSL), 2025)
This research is motivated by the urgent need for educational leadership that can foster moderate attitudes amidst ideological challenges and social pressures in Islamic educational institutions. The goal is to develop a centralized disciplinary leadership model that is effective in promoting religious moderation at MTs Gondang, Pekalongan. Using a qualitative case study design, the research collected data through participant observation, in-depth interviews with the principal, teachers, and staff, as well as an analysis of policy documents and training programs. Data analysis followed the Miles and Huberman model. The results indicate that centralized disciplinary leadership is implemented in a humanistic (rather than authoritarian) manner through a coaching approach based on advice, counseling, and mentoring. While hierarchical supervision ensures consistency, it has the potential to limit teacher creativity and foster dependency. Key challenges arise from the dominance of textual approaches, internal resistance, and pressure from conservative communities that hinder the critical internalization of moderate values.